The Effect Of Cashless Transactions On The Velocity Of Money In Indonesia - Diva Delia Rossa Nicolas; Sishadiyati, Sishadiyati (International Journal of Economics, Business and Innovation Research, 2025)
Technological developments in the financial sector have encouraged a shift in transactions from cash to cashless. The increasingly massive digitization of the payment system is expected to affect the velocity of money in the economy, which is reflected in the velocity of money. This study aims to analyze the effect of cashless transactions on the velocity of money in Indonesia. Using secondary data from Bank Indonesia and the Central Bureau of Statistics, this study applies quantitative methods to measure the relationship between the volume of cashless transactions and the velocity of money. The results show that an increase in cashless transactions has a positive correlation with the velocity of money, indicating that the digitization of the payment system can accelerate the velocity of money in the economy. The findings provide implications for monetary policy and payment system regulation in supporting economic efficiency in the digital era.